Feed and Lead: Paradigms of Psycho-Social Dimensions of Christian Leadership in Eastern Theological Perspective - Thattacherry, Manoj John (Asian Horizons, 2024)
Christian Leadership has always been held in high esteem and has remained a subject for consideration by others. The fundamental thrust of this leadership is that it is a worldly leadership which is thoroughly Christ- centered. We can find some paradigms of the background to the present- day Christian leadership among the ancient Syriac Church Fathers. One such Syriac scholar is Aphrahat. The 10th tahwita ‘On Shepherds’ throws ample light on the paradigms of psycho-social dimensions of Christian leadership. This article attempts to introduce the excellent models of Christian leadership which emerge in the 10th tahwita.